Sur la convergence des séries d’interpolation - Nasekovskaja, N. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Н. С. Насековская. О сходимости интерполяционных рядовN. Nasekovskaja. Interpoliacinių eilučių konvergencija